Distinct Molecular Mechanisms Underlying Potassium Efflux for NLRP3 Inflammasome Activation - Xu, Ziwei; Chen, Zi-mo; Wu, Xiaoyan; Zhang, Linjie; Cao, Ying; Zhou, Pingzheng (Frontiers in Immunology, 2020)
The NLRP3 inflammasome is a core component of innate immunity, and dysregulation of NLRP3 inflammasome involves developing autoimmune, metabolic, and neurodegenerative diseases. Potassium efflux has been reported to be essential for NLRP3 inflammasome activation by structurally diverse pathogen-associated molecular patterns (PAMPs) or danger-associated molecular patterns (DAMPs). Thus, the molecular mechanisms underlying potassium efflux to activate NLRP3 inflammasome are under extensive investigation. Here, we review current knowledge about the distinction channels or pore-forming proteins underlying potassium efflux for NLRP3 inflammasome activation with canonical/non-canonical signaling or following caspase-8 induced pyroptosis. Ion channels and pore-forming proteins, including P2X7 receptor, Gasdermin D, pannexin-1, and K2P channels involved present viable therapeutic targets for NLRP3 inflammasome related diseases.